Decision Support System for Volunteer Selection for Archipelago Marine Volunteers (Rapala) Using the Profile Matching Method - Hozairi; juhairiyah; Makruf , Masdukil; Alim, Syariful (Association for Scientific Computing Electrical and Engineering, 2024)
This study aims to develop a Decision Support System (DSS) for selecting candidates for Archipelago Sea Rangers Volunteers (RAPALA) using the profile matching method. Bakamla RI, as an institution responsible for maritime security in Indonesian territorial waters, requires prospective RAPALA volunteers who are qualified and have the appropriate competence to protect the archipelago's seas, which are increasingly threatened. In this study, a decision support system was developed that can compare the profiles of prospective volunteers with predetermined criteria. This system aims to improve efficiency and accuracy in the selection process for volunteer candidates, as well as strengthen selection criteria and methods based on appropriate profiles. To create a decision support system, the profile matching method is used. Profiles of prospective volunteers are assessed based on factors such as intelligence, work attitude, behavior, and domicile. This study shows that the RAPALA-1 candidate is ranked first with a score of 4.76, the RAPALA-2 candidate is ranked second with a score of 4.49, and the RAPALA-3 candidate is ranked third with a score of 4.26. It is hoped that with this decision-support system, the selection process for RAPALA volunteer candidates can be carried out more efficiently and objectively. The selected volunteer candidates are expected to have the right skills and motivation to maintain the security and preservation of the archipelago's seas. This will contribute to increasing the security and sustainability of marine resources in Indonesia.